2022
DOI: 10.34068/joe.60.03.11
|View full text |Cite
|
Sign up to set email alerts
|

Minnesota Cottage Food Industry: Insights from Extension Food Safety Education

Abstract: The cottage food industry has become a significant part of the food supply in Minnesota, most likely as a result of the growing consumer demand for locally produced, minimally processed and value-added foods. Using post-training evaluations, we characterized the cottage food producers in Minnesota and assessed the impact of our food safety course. The results showed that the producers are mostly white women (71%), producing and selling a variety of products. The learners gained knowledge to safely produce and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…For example, two indicated they were fully or partially covered by FSMA but also indicated they sold less than $25,000 per year of produce, although any grower who sells less than $25,000 per year of produce is not covered by FSMA. In a study evaluating produce farmers in Minnesota, Omolo (12) noted this lack of synergy as well and suggested that it may be as a result of challenges in understanding the exemption criteria for the FSMA PSR.…”
Section: Discussionmentioning
confidence: 99%
“…For example, two indicated they were fully or partially covered by FSMA but also indicated they sold less than $25,000 per year of produce, although any grower who sells less than $25,000 per year of produce is not covered by FSMA. In a study evaluating produce farmers in Minnesota, Omolo (12) noted this lack of synergy as well and suggested that it may be as a result of challenges in understanding the exemption criteria for the FSMA PSR.…”
Section: Discussionmentioning
confidence: 99%